(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article is about the forming motivation, types of motivation, reasons to increase motivation, the techniques to use in elementary school. Moreover, discusses the concepts of motive and motivation and identifies explanations for motives of primary schoolchildren age.